Menopausal experience among postmenopausal women in Kuantan, Pahang - A qualitative study - Jamani, Nurjasmine Aida; Mohamad Ishak, Nurul Najmi; Abdul Hadi, Azwanis; Abd. Aziz, Karimah Hanim; Mohd Arifin, Siti Roshaidai (2019)
Background: Menopause signifies the beginning of a non-reproductive phase from the reproductive period. Menopausal experiences and symptoms vary across the cultures and countries. It is very imperative to understand how menopause both enriches and challenges women’s lives.